Golf, enterprise, and tourism in Belle Époque Europe c. 1900–1914*. Issue 2 (4th May 2019) - Rebanal Martínez, Gerardo
ABSTRACT: Golf was largely regarded as just another sport customarily linked with the overall development of resorts in the Belle Époque. On some occasions the sport played a central role in the promotional aspects of holiday destinations, especially when it originated in companies with a general interest in the resort; on other occasions, it was organised by those wintering there who were either subsidised by external funds or, more rarely, living on their own resources. Golf began to be perceived not only as another outdoor recreational activity and amateur/professional sport but as a valuable source of income from attracting and retaining holidaymakers. This article is focused on some places in the Atlantic Europe region during the Belle Époque, places in which golf was appreciated in both a convivial and commercial sense. The article discusses Walton Heath and Hastings in Britain; Le Touquet, Arcachon and Hendaye in France; San Sebastián in Spain; and Estoril in Portugal. The golf courses at these resorts – or urban developments like Walton Heath – were not isolated members' clubs, as many golf clubs were then, but fundamental features in the life of such resorts that offered new experiences to avid travelling sports enthusiasts.